Penerapan Model Pembelajaran Berbasis Masalah Berbantuan Teknik ATM Untuk Meningkatkan Prestasi Belajar Siswa - I Wayan Kerti (Jayapangus Press, 2021)
This study is aimed at increasing students’ learning achievement with two cycles research plan. The Subject of the study are 31 students. They are 15 male; and 16 female students. The learning achievement data are collected by using observation sheet, multiple choice test, and essay test. The data are analyzed with descriptive qualitative method. The result of the study shows that the implementation of Problem Based Learning Model with ATM technique increased the students’ learning. At the first observation data, students achievement in affective aspect students who are master 51.61%, students who have not master 48.39%; at the cognitive aspect the mean 61, the classical mastery 38.71%; at the mean of psychomotor aspect 68, classical mastery 54.84%. At cycle I the learning achievement in affective aspect 58.06%, students who have not master 41.94%; the mean of learning achievement at the cognitive aspect 89.68, classical mastery 100% the mean of learning achievement in psychomotor aspect 74.84, classical mastery 77.42%. At cycle II the learning achievement at the affective aspect Siklus II 96.77; the mean of learning achievement in cognitive aspect 84.44, classical mastery 97.09;the lmean of earning achievement in psychomotor aspect 81.77, classical mastery 100 Based on the result of the study it is suggested; (1) For Students can use this learning model to increase their learning achievement; (2) Other teachers can implement this learning model by considering the weakness of the result of the study; (3) School can use this learning model to elaborate and solve the learning problem in the class (4) Other researcher can use this research as a relavant study